Explaining the presence of political content in football fans’ antagonistic communication in Cyprus - Stylianou, Stelios; Theodoropoulou, Vivi (My University, 2019)
The landscape of football fan culture in Cyprus contains a good deal of antagonistic communicative actions of explicit political content. We attempt to explain this phenomenon by focusing on two analytical dimensions. First, we ask to what extent are political elements in fans’ antagonistic communication guided by politics, in the narrower sense, that is, political ideology, party affiliation, historical narratives, etc.—the political–historical dimension. Second, we ask to what extent are these political elements means of performance in an intense game of identity reaffirmation—the game dimension. We address these questions qualitatively, using data from 20 field observations of first division football games and from 38 in-depth interviews, predominantly with football fans. We conclude that both dimensions are meaningful and useful in explaining football fans’ antagonistic communication.
Keywords: Binary oppositions; Fandom; Football; Identity; Ieft vs. right; Politics